Probabilistic optimal siting and sizing of distributed generation and shunt capacitors considering feeder flow control units using a novel distribution power flow - Gupta S.; Maulik A.; Das D.; Singh A. (My University, 2025)
A modern energy system should be reliable, economically viable, and environment-friendly. This paper addresses the above issue by proposing a probabilistic approach of optimally placing and sizing distributed generation and shunt capacitors in a distribution network. Objectives are to simultaneously reduce the cost, emission, network loss, improve the system voltage profile, and avoid line overloads. A feeder flow control generator is considered so that the distribution network draws a constant amount of active and reactive power from the substation. The operation is modelled using a Zero-PQVδ bus pair in the power flow. A novel distribution system power flow is proposed to embody the operation philosophy. Uncertainties of renewable power sources and load demand are modelled using ‘Hong's 2 m point estimate method’. A fuzzy multi-objective satisfaction criterion is used to realise multiple objectives. Simulation studies on a thirty-three node distribution network reveal the efficacy of the proposed method. © 2022 Informa UK Limited, trading as Taylor & Francis Group.